2007
DOI: 10.1093/hmg/ddm174
|View full text |Cite
|
Sign up to set email alerts
|

An SNP in the 5′-UTR of GDF5 is associated with osteoarthritis susceptibility in Europeans and with in vivo differences in allelic expression in articular cartilage

Abstract: A compelling genetic association with osteoarthritis (OA) of a functional SNP (rs143383, T/C) in the 5'-UTR of the GDF5 gene was recently reported in case-control cohorts from Japan and China. GDF5 is a pro-chondrogenic growth factor. The T-allele frequency of the gene was elevated in cases, with an odds ratio (OR) of 1.79, and in vitro functional studies demonstrated that this allele mediated a moderate but significant reduction in the activity of the GDF5 promoter in several cell lines. Our initial objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
173
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 195 publications
(191 citation statements)
references
References 23 publications
16
173
1
1
Order By: Relevance
“…Consistent with the previous reports in Caucasian and Orientals (Miyamoto et al, 2007;Southam et al, 2007), the present study has demonstrated the association between polymorphisms of GDF5 and risk of knee OA in North Indian population and supports the hypothesis that polymorphisms in GDF5 may be involved in the pathogenesis of this disease (Miyamoto et al, 2007). Our data have shown that polymorphism exist in the GDf-5 (BsiE1) gene in North Indian population.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with the previous reports in Caucasian and Orientals (Miyamoto et al, 2007;Southam et al, 2007), the present study has demonstrated the association between polymorphisms of GDF5 and risk of knee OA in North Indian population and supports the hypothesis that polymorphisms in GDF5 may be involved in the pathogenesis of this disease (Miyamoto et al, 2007). Our data have shown that polymorphism exist in the GDf-5 (BsiE1) gene in North Indian population.…”
Section: Discussionsupporting
confidence: 92%
“…Our data have shown that polymorphism exist in the GDf-5 (BsiE1) gene in North Indian population. The frequency of T allele in our population (55%) was similar to that reported in Caucasians (59-63 %) (Rouault et al, 2010;Southam et al, 2007;Tsezou et al, 2008;Valdes and Spector, 2009) the oriental population carry relatively higher frequency (70-74%) of variant T allele (Shin et al, 2012;Cao et al, 2010;Dai et al, 2008;Miyamoto et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…28 The most associated SNP (rs143383) is a functional variant, and the susceptibility allele shows decreased GDF5 transcription in vitro and in vivo. [28][29][30] The same allele was reported to be associated with adult height in Caucasians through a GWAS using subjects with non-insulin-dependent diabetes mellitus. 31 Valdes et al 32 assessed rs143383 for OA in the UK Caucasians using 999 knee OA, 843 hip OA and 1166 control samples, and they replicated the association of GDF5 in knee OA (OR¼1.29, 95% CI of 1.14-1.47; P¼8Â10 À5 ).…”
Section: Gdf5mentioning
confidence: 78%